Prevalence and factors associated with modern contraceptive discontinuation among women of reproductive age (15-49) in Burera District, Rwanda 2025 - Egide Karangwa; Charles Nsanzabera (Journal of African Epidemiology and Public Health Sciences, 2026)
Background: Modern contraceptive discontinuation remains a major public health concern because it increases the risk of unintended pregnancies, unsafe abortions, and maternal and infant morbidity and mortality. Despite increased contraceptive uptake in Rwanda, discontinuation remains a challenge, particularly in rural areas. This study assessed the prevalence and factors associated with of modern contraceptive discontinuation among women of reproductive age in Burera District, Rwanda. Methods: A cross-sectional study was conducted among 398 women of reproductive age who had used modern contraceptive methods. Data were collected using a structured questionnaire and analyzed using SPSS version 25. Descriptive statistics summarized participant characteristics. Chi-square tests assessed associations between variables and contraceptive discontinuation. Logistic regression was used to estimate crude and adjusted odds ratios (AORs) with 95% confidence intervals (CIs). Results: The prevalence of modern contraceptive discontinuation was 33.4% (95% CI: 28.9–38.2). Women from households with a monthly income above 50,000 RWF had significantly lower odds of discontinuation than those earning 0–50,000 RWF. Women with five or more children were more likely to discontinue contraception (AOR=4.16; 95% CI: 1.17–14.78), while those who wanted no more children were less likely to discontinue use (AOR=0.37; 95% CI: 0.18–0.75). Women who did not receive family planning counselling had higher odds of discontinuation (AOR=3.44; 95% CI: 1.33–8.93). The main reasons for discontinuation were the desire to become pregnant (46.6%), side effects (27.1%), and fear of side effects (10.5%). Conclusion: Modern contraceptive discontinuation remains substantial in Burera District and is influenced by household income, parity, fertility intentions, and family planning counselling. Strengthening counselling services and addressing contraceptive side effects may improve contraceptive continuation and reproductive health outcomes. Keywords: Contraceptive discontinuation, Modern contraceptive, Associated factor, Rwanda